The Effect of Starter Concentration and Fermentation Period of Cocoa Pulp on Ethanol Production - Yumas, Medan; Rosniati, Rosniati (Biopropal Industri, 2014)
The study of starter concentration effect and fermentation period of cocoa pulp on ethanol production has been carried out in order to determine the concentration of Saccharomyces cereviceae as a starter and optimum fermentation period to produce bioethanol from cocoa pulp. Variables in this research were S. cereviceae consentration of 6, 7, 8 and 9%; and fermentation periods 3, 5 and 7 days. The results showed that 5 days of fermentation period and the addition of S. cereviseae with a concentration of 9% obtained the highest ethanol content as much as 5.93% by the end of fermentation acidity of 6.0.